Exploring The Impact of MBKM Program To The Learners Academic Quality - Pasoloran Pongsapan, Nehru; Veronika, Veronika; Markus Deli Girik Allo (Universitas Cokroaminoto Palopo, 2024)
The objective of this research was to find out how is the impact of MBKM program to the learners academic quality after participating in the MBKM program. In carrying out this research, the researcher used describe qualitative research. The purpose sampling strategy was used obtain data from six (6) learners of the English Education Study Program at Universitas Kristen Indonesia Toraja class of 2020 who had pariticpated in the MBKM program. Data were obtained using observation, interview and document file analysis techniques. Based on the results of the research, the researcher concluded that the MBKM program has a positive impact to the learners academic quality in the English Education Study Program at Universitas Kristen Indonesia Toraja. These results are shown by the experience by learners after participating in the MBKM program both when studying in campus and also teaching practice outside campus so that they experience improvements therefore, understanding concepts, the ability to think critically in solving a problem, develop skills obtained, motivation and independence in learning, fun learning experiences, participation in academic activities that can train leadership skills, academic achievement and career adaptability. Through the MBKM program learners can improve their academic quality gradually, especially as future English teachers. There are some obstacles in the implementation of the MBKM program and for this reason it is hoped that there will be an evaluation related to the program, so that learners and university can be of mutual quality.